A model for an interconnected photovoltaic system using an off-grid inverter as a reference node in island mode (2019)
This paper presents the results of a research work where an intentional connection is made in island mode, a low power isolated photovoltaic system (300W) is used as a reference for an interconnected photovoltaic system (1,270W). The objective is to configure an islanded system that does not require the main grid to generate the synchronization parameters for grid-tie inverters to operate. This work presents suitable building block models (converters, inverters and LCL filters) that can be used to design of a control scheme that can maintain performance parameters such as % THD and RMS level of the voltage in the load according to the IEEE-Std-1159-1995 standard. The control system is based on an intelligent controller using the technique of artificial neural networks, for the activation and deactivation of ballast loads to maintain the voltage level at 120VRMS and balance the active power produced by the interconnected system and the active power consumed by the load. In addition to the mentioned power-system performance parameters, the work focuses on evaluating response times of the intelligent controller to number of ballasts loads according to the power consumed by the load. The tests are made in scenarios of stability and variation in solar radiation, the power produced by the interconnected system and the power consumed by the load. The complete system can be configured with standard commercial devices which do not require advanced or complex operation techniques in inverters, converters and filters.